(untitled) (Physical Education, Health and Social Sciences, 2025)
Parental involvement involves the participation of parents in regular, two ways, meaningful communication, involving student’s academic learning and other school activities. The purpose of this study was to find out the perceptions and role of parents in enhancing children academic achievement. This study explored the relationship between parental involvement in primary school level and student achievement. The objectives of the study were: to modernize and strengthen the system for parental involvement in school education, to engage parents meaningfully in the education of their children and in the school community. The study was descriptive in nature. The primary schools located in Rawalpindi region were participated for the population in this study. A total of 60 parents were chosen for the sample. Parents of primary level students filled the questionnaire. Convenient sampling techniques were used to select the sample of the study. Twelve primary schools were selected from the identified population. A close ended questionnaire was developed for collecting the data. Mean test was applied for getting responses from the participants. Results shows that Parental involvement has a positive role for students’ academic achievement at primary students. Highly engaged parents tend to achieve higher academically compared to those with less involved parents’ involvement level. This research recommended that for promoting parental involvement in school’s different activities and events were held.